2018
DOI: 10.1590/1413-81232018234.14082016
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of accesses to information on breast cancer and screening on the Brazilian National Cancer Institute website: an exploratory study

Abstract: Delays in diagnosis due to low Breast Cancer awareness are widespread in Brazil maybe owing to ineffective strategies to raise attention on early diagnosis. As a proxy of collective interest in BC screanning (BCS) we studied the monthly accesses to BC and BCS webpages in INCA's website along 48 months. A log analyzer built a time serie (2006-2009) of BC and BCS monthly means, which oscilations were studied by analysis of variance (ANOVA). We found significant increasing accesses to BC and transient "attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
3
0
5
Order By: Relevance
“…Moreover, a study conducted in Hungary revealed most respondents were unaware of the fact that breast cancer self-examination should be initiated two decades earlier than mammography, when women turn twenty years old [ 42 ]. The lack of knowledge and awareness on breast cancer is also an identified concern in a number of highly populated countries, such as Ethiopia [ 43 ], Nigeria [ 44 ], and Brazil [ 45 ]. A systematic review of breast cancer screening discourse on social media [ 46 ] indicates there is a substantial presence of unscientific statements shared by lay individuals about the topic, such as “mammography causes breast cancer”, or “breast cancer can be prevented by organic food”.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study conducted in Hungary revealed most respondents were unaware of the fact that breast cancer self-examination should be initiated two decades earlier than mammography, when women turn twenty years old [ 42 ]. The lack of knowledge and awareness on breast cancer is also an identified concern in a number of highly populated countries, such as Ethiopia [ 43 ], Nigeria [ 44 ], and Brazil [ 45 ]. A systematic review of breast cancer screening discourse on social media [ 46 ] indicates there is a substantial presence of unscientific statements shared by lay individuals about the topic, such as “mammography causes breast cancer”, or “breast cancer can be prevented by organic food”.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in breast cancer always outperformed (in absolute and relative terms) mammography, but showed erratic patterns over the years and irregular growth in annual means. This may be consequent to events without seasonality, linked to the high incidence of new cases and constant media coverage—especially among celebrities who seem to boost the number of hits [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports in the literature concerning campaigns and health interventions based on “what” and “how” (selection of qualified information and proper vehicles to deliver messages) [ 35 , 36 ], “where” (environments in which campaigns would be more effective) [ 37 , 38 ], and “who” (who are the best counselors) [ 30 , 39 , 40 ]. Nonetheless, reports based on “when”—the ideal timing for intervention—are not so frequent.…”
Section: Discussionmentioning
confidence: 99%
“…O papel da mídia na comunicação sobre o câncer de mama vem sendo problematizado em estudos em nível internacional (ABIGHANNAM; CHILEK; KOH, 2018) e nacional (SIMEÃO et al, 2016;VASCONCELLOS-SILVA;SORMUNEN;CRAFTMAN, 2018). Porém, a temática específica que envolve a detecção precoce, e especialmente as questões contemporâneas sobre o rastreamento mamográfico, são ainda pouco estudadas.…”
Section: Introductionunclassified